Genome‐wide scans between two honeybee populations reveal putative signatures of human‐mediated selection. (4th September 2017) - Parejo, M.; Wragg, D.; Henriques, D.; Vignal, A.; Neuditschko, M.
Summary: Human‐mediated selection has left signatures in the genomes of many domesticated animals, including the European dark honeybee, Apis mellifera mellifera, which has been selected by apiculturists for centuries. Using whole‐genome sequence information, we investigated selection signatures in spatially separated honeybee subpopulations (Switzerland, n  =   39 and France, n  =   17). Three different test statistics were calculated in windows of 2 kb (fixation index, cross‐population extended haplotype homozygosity and cross‐population composite likelihood ratio) and combined into a recently developed composite selection score. Applying a stringent false discovery rate of 0.01, we identified six significant selective sweeps distributed across five chromosomes covering eight genes. These genes are associated with multiple molecular and biological functions, including regulation of transcription, receptor binding and signal transduction. Of particular interest is a selection signature on chromosome 1, which corresponds to the WNT4 gene, the family of which is conserved across the animal kingdom with a variety of functions. In Drosophila melanogaster, WNT4 alleles have been associated with differential wing, cross vein and abdominal phenotypes. Defining phenotypic characteristics of different Apis mellifera ssp., which are typically used as selection criteria, include colour and wing venation pattern. This signal is therefore likely to be a good candidate for human mediated‐selection arising from different applied breeding practices in the two managed populations.